Analysis of key aroma-active compounds in cooked river snail (Sinotaia quadrata) meat - Jingyu Yao; Liqiong Wen; Li Ling; Peng Wan; Rui Wang; Weiliang Guan; Qinzhi Wang; De-Wei Chen (Applied Food Research)
River snail meat is a key ingredient of Liuzhou river snails rice noodles (Luosifen), which contributes unique fresh and green notes to the soup of the noodles. In this study, vacuum simultaneous steam distillation extraction (V-SDE) was used to extract the volatile components in cooked river snail meat, and then gas chromatography-mass spectrometry combined with olfactometry (GC-MS-O) was used to characterize the key aroma-active compounds. A total of 88 volatile compounds were detected, and most of the volatile compounds contained in cooked river snail meat were related to lipid oxidative degradation. A total of 27 aroma-active compounds were identified. Among them, (E,E)-2,4-decadienal, 1-hepten-3-one, (E,E)-2,4-nonadienal, 2-isopropyl-3-methoxypyrazine, 1-octen-3-ol, (Z)-4-decenal, (E)-2-octenal and octanal, were of higher flavor dilution factor and odor activity value, and they were considered as the key aroma-active compounds. This study characterizes the aroma-active compounds in the cooked river snail meat.